Lump in the Muscle: Should We Forget a Rare Cause? - Sidhu, Amitoj; Chopra, Preeyati; Chopra, Vishal (International Journal of Medical Students, 2025)
BACKGROUND: Cysticercosis is a parasitic disease caused by the larval form of Taenia solium (pig tapeworm). It most commonly affects the human nervous system. Isolated involvement of the muscle is rare and only sporadic case reports are available. THE CASE: A 49-year-old male presented with pain and swelling in the right lateral infraclavicular area for 2 weeks. The swelling was well defined, 2×1.5 cm in size, firm on palpation and immobile. It was non fluctuant and non-reducible with no tenderness or overlying skin changes. There was no other swelling on the body. The patient complained of mild pain on movement of the right arm especially on overhead abduction but without any neurological involvement. There was no history of fever, cough or any recent sick contacts. There was a history of neurocysticercosis in the past. Rest of the physical examination and laboratory results were within normal limits. Ultrasonography showed a cyst with an echogenic scolex and an inflammatory mass surrounding it. Magnetic resonance imaging showed a 15×10×9mm cystic mass in the right pectoralis major muscle, accompanied by scolex, muscular oedema, and subcutaneous oedema. The patient refused surgical intervention. He was started on albendazole for two weeks to expedite cyst involution and corticosteroids to minimize inflammation around the lesion. Steroids were stopped after two weeks and Albendazole was continued for three months. The patient showed complete resolution of the swelling after 3 months. This case highlights the need of investigating intramuscular cysticercosis as a possible diagnosis for individuals with a single intramuscular or subcutaneous mass. Early suspicion of cysticercosis especially in endemic areas is important, to distinguish it from various similar conditions. CONCLUSION: The diagnosis of intramuscular cysticercosis is frequently delayed or overlooked due to vague clinical symptoms. Clinically, the diagnosis of intramuscular cysticercosis might be problematic because there are various clinical differentials, including epidermoid cysts, lipoma, sarcoma, neuroma, neurofibromas, cold abscess, and pyomyositis. Therefore, radiological evaluation is at times the only diagnostic modality especially when patient refuses surgical intervention.